The Dissemination of Synbiotic Tempe Extract Krenova Soygurt Products as Functional Drinks for Stunting Prevention through Community Partnership Programs - Agnes Sri Harti; Mellia Silvy Irdianty; Nurul Devi Ardiani; Bambang Abdul Syukur; Yusup Subagio Sutanto (CV Media Inti Teknologi, 2024)
This activity aimed to educate the public about Synbiotic Tempe Extract Krenova Soygurt Products as Functional Drinks for Stunting Prevention. The implementation of activities as community service in the form of health education and counseling on stunting prevention involved 10 lecturers, 12 students along with 9 cadres and 30 people from the Cempaka Integrated Health Post, Wonorejo Village, Gondangrejo, Karanganyar Regency. The social community activity was carried out on August 26, 2024, and the community received a response and enthusiasm through active participation and involvement in the discussion and question and answer sessions. The essence of the implementation and dissemination of the benefits of synbiotic soygurt tempeh can function as a functional drink based on science and technology, halal and economical through a community partnership program carried out sustainably, completely, and meaningfully at the Cempaka Integrated Health Post, Wonorejo Village, Gondangrejo District, Karanganyar Regency to achieve the target of down streaming Kreova health products that are beneficial to the community and support the success of the Government's program in overcoming and reducing the incidence of stunting in Indonesia.